Postoperative Adjuvant Treatment in Women with Stage I Endometrial Cancer: A Retrospective Study - Peiying Fu; Haiying Sun; Ting Zhou; Pengfei Cui; Shixuan Wang; Ronghua Liu (International Journal of Clinical Practice)
Objective. To evaluate whether postoperative adjuvant treatment is beneficial for patient survival after surgery for early stage endometrial cancer (EC). We analyzed the outcomes of patients treated with radiotherapy, chemotherapy, or progestagen combined with other adjuvant treatments. Methods. We analyzed the outcomes of patients treated with radiotherapy alone, chemotherapy alone, or progestagen treatment with other adjuvant treatments. Women without any adjuvant treatment after operation were used as controls. We retrospectively examined disease-free survival (DFS), overall survival (OS), and high-risk factors that affected the survival status of all patients who received different postoperative adjuvant therapies. Results. In all 192 patients, the total relapse and mortality rates were 5.57% and 1.68%, respectively. Fourteen patients (7.29%) developed isolated local recurrence, and 2 patients died (1.04%) of recurrence during the follow-up period. The 5-year DFS and OS rates of all patients were 95.83% and 93.75%, respectively. No significant differences were observed in the 5-year DFS, 5-year OS, OS, or DFS among the four groups of patients with FIGO stage I endometrial cancer (P=0.9849, 0.7430, 0.9754, and 0.4534, respectively). The differences in the log-rank test results of the estimates of the 5-year DFS, 5-year OS, DFS, and OS of patients with different disease stages and different ages were all significant, but no differences were observed in these parameters among patients with varying degrees of differentiation. Histologic grade, CA125 level, ER and PR status, and adjuvant therapy had no significant effect on the DFS and OS of all patients according to univariate and multivariate regression analyses, but a significant effect on DFS and OS was found when the patients were stratified by age. Conclusion. This retrospective study showed that adjuvant therapy after surgery was not significantly associated with improved DFS or OS in patients with early stage endometrial cancer. However, FIGO stage and age affected the survival of patients with stage I endometrial cancer.